1999
DOI: 10.1097/00041327-199906000-00010
|View full text |Cite
|
Sign up to set email alerts
|

MR Changes in the Calcarine Area Resulting From Retinal Degeneration

Abstract: PURPOSE:To study MR images for atrophic changes in the calcarine area resulting from retinal degeneration. METHODS: MR images from nine patients with retinal degeneration confirmed by ophthalmologic examination and from 30 healthy volunteers were reviewed. The causes of retinal degeneration were hereditary pigmentary degeneration of the retina (four patients), high myopia (two patients), and chorioretinal atrophy (three patients); all patients had visual disturbances and visual field abnormalities. To estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 10 publications
4
26
0
Order By: Relevance
“…Previous studies with low vision patients with glaucoma and macular degeneration reported reduced gray matter volume in occipital cortex consistent with the visual field scotomata (Bogorodzki et al, 2014, Boucard et al, 2009, Burge et al, 2016, Chen et al, 2013, Gupta et al, 2006, Hernowo et al, 2014, Kitajima et al, 1997, Kitsos et al, 2009, Olivo et al, 2015, Plank et al, 2011, Prins et al, 2016a, Prins et al, 2016b, Yu et al, 2014, Yu et al, 2013, Zikou et al, 2012). Retinal ganglion cell degeneration in glaucoma, and also in macular degeneration after photoreceptors death, may cause transneuronal degeneration along visuo-cortical pathways, leading to neuronal atrophy in visual cortex.…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies with low vision patients with glaucoma and macular degeneration reported reduced gray matter volume in occipital cortex consistent with the visual field scotomata (Bogorodzki et al, 2014, Boucard et al, 2009, Burge et al, 2016, Chen et al, 2013, Gupta et al, 2006, Hernowo et al, 2014, Kitajima et al, 1997, Kitsos et al, 2009, Olivo et al, 2015, Plank et al, 2011, Prins et al, 2016a, Prins et al, 2016b, Yu et al, 2014, Yu et al, 2013, Zikou et al, 2012). Retinal ganglion cell degeneration in glaucoma, and also in macular degeneration after photoreceptors death, may cause transneuronal degeneration along visuo-cortical pathways, leading to neuronal atrophy in visual cortex.…”
Section: Discussionmentioning
confidence: 62%
“…These studies have demonstrated that disruption of visual input can lead to atrophic changes including the visual pathway and early visual cortical areas, whereas the spread of atrophy to higher cortical areas has not been demonstrated consistently (Boucard et al 2009; Chan et al 2004; Hernowo et al 2011; 2013; Kitajima et al 1997; Mendola et al 2005; Parravano et al 1993; Plank et al 2011; von dem Hagen et al 2005). These extrastriate areas could provide the main substrate for visual imagery in SH.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, plasticity may lead to changes in cortical thickness in the early blind. In addition, transneuronal degeneration occurs in some blind subjects with optic nerve atrophy and optic nerve hypoplasia and might result in visual cortex atrophy in these subjects (Kitajima et al, 1997). This could lead to a reduction in cortical thickness in the early blind.…”
Section: Introductionmentioning
confidence: 99%